Functional Characterization of a Syntaxin Involved in Tomato (Solanum lycopersicum) Resistance against Powdery Mildew - Bracuto, Valentina; Appiano, Michela; Zheng, Zheng; Wolters, Anne-Marie A.; Yan, Zhe; Ricciardi, Luigi; Visser, Richard G. F.; Pavan, Stefano; Bai, Yuling (Frontiers in Plant Science, 2017)
Specific syntaxins, such as Arabidopsis AtPEN1 and its barley ortholog ROR2, play a major role in plant defence against powdery mildews. Indeed, the impairment of these genes results in increased fungal penetration in both host and non-host interactions. In this study, a genome-wide survey allowed the identification of 21 tomato syntaxins. Two of them, named SlPEN1a and SlPEN1b, are closely related to AtPEN1. RNAi-based silencing of SlPEN1a in a tomato line carrying a loss-of-function mutation of the susceptibility gene SlMLO1 led to compromised resistance towards the tomato powdery mildew fungus Oidium neolycopersici. Moreover, it resulted in a significant increase in the penetration rate of the non-adapted powdery mildew fungus Blumeria graminis f. sp. hordei. Codon-based evolutionary analysis and multiple alignments allowed the detection of amino acid residues that are under purifying selection and are specifically conserved in syntaxins involved in plant-powdery mildew interactions. Our findings provide both insights on the evolution of syntaxins and information about their function which is of interest for future studies on plant-pathogen interactions and tomato breeding.